Building the e-World Ecosystem 11th IFIP WG 6.11 Conference on e-Business, e-Services, and e-Society, I3E 2011, Kaunas, Lithuania, October 12-14, 2011, Revised Selected Papers - Skersys, Tomas; Butleris, Rimantas; Nemuraite, Lina; Suomi, Reima (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 11th IFIP WG 6.11 Conference on e-Business, e-Services and e-Society, I3E 2011, held in Kaunas, Lithuania, in October 2011. The 25 revised papers presented were carefully reviewed and selected from numerous submissions. They are organized in the following topical sections: e-government and e-governance, e-services, digital goods and products, e-business process modeling and re-engineering, innovative e-business models and implementation, e-health and e-education, and innovative e-business models.